Biallelic MADD variants cause a phenotypic spectrum ranging from developmental delay to a multisystem disorder - Schneeberger, Pauline E; Kortüm, Fanny; Korenke, Georg Christoph; Alawi, Malik; Santer, René; Woidy, Mathias; Buhas, Daniela; Fox, Stephanie; Juusola, Jane; Alfadhel, Majid; Webb, Bryn D; Coci, Emanuele G; et al. (Brain, 2020)
In pleiotropic diseases, multiple organ systems are affected causing a variety of clinical manifestations. Here, we report a pleiotropic disorder with a unique constellation of neurological, endocrine, exocrine, and haematological findings that is caused by biallelic MADD variants. MADD, the mitogen-activated protein kinase (MAPK) activating death domain protein, regulates various cellular functions, such as vesicle trafficking, activity of the Rab3 and Rab27 small GTPases, tumour necrosis factor-α (TNF-α)-induced signalling and prevention of cell death. Through national collaboration and GeneMatcher, we collected 23 patients with 21 different pathogenic MADD variants identified by next-generation sequencing. We clinically evaluated the series of patients and categorized the phenotypes in two groups. Group 1 consists of 14 patients with severe developmental delay, endo- and exocrine dysfunction, impairment of the sensory and autonomic nervous system, and haematological anomalies. The clinical course during the first years of life can be potentially fatal. The nine patients in Group 2 have a predominant neurological phenotype comprising mild-to-severe developmental delay, hypotonia, speech impairment, and seizures. Analysis of mRNA revealed multiple aberrant MADD transcripts in two patient-derived fibroblast cell lines. Relative quantification of MADD mRNA and protein in fibroblasts of five affected individuals showed a drastic reduction or loss of MADD. We conducted functional tests to determine the impact of the variants on different pathways. Treatment of patient-derived fibroblasts with TNF-α resulted in reduced phosphorylation of the extracellular signal-regulated kinases 1 and 2, enhanced activation of the pro-apoptotic enzymes caspase-3 and -7 and increased apoptosis compared to control cells. We analysed internalization of epidermal growth factor in patient cells and identified a defect in endocytosis of epidermal growth factor. We conclude that MADD deficiency underlies multiple cellular defects that can be attributed to alterations of TNF-α-dependent signalling pathways and defects in vesicular trafficking. Our data highlight the multifaceted role of MADD as a signalling molecule in different organs and reveal its physiological role in regulating the function of the sensory and autonomic nervous system and endo- and exocrine glands.
Keywords: fenotyp; Phenotype; mutace; whole-exome sequencing; signální transdukce; Nervous System Diseases; nemoci nervového systému; intellectual disability; Guanine Nucleotide Exchange Factors; Signal Transduction; DENN; signální adaptorové proteiny receptorové domény smrti; Death Domain Receptor Signaling Adaptor Proteins; HSAN; lidé; Humans; výměnné faktory guaninnukleotidů; multisystem; Protein Transport; vývojové poruchy u dětí; Mutation; transport proteinů; Developmental Disabilities